The Effects of Emotional Design on Multimedia Learning and Appreciation of Chinese Poetry - Wang, Yi; Zhou, Zhijin; Gong, Shaoying; Jia, Dandan; Lei, Jing (Frontiers in Psychology, 2021)
Painting, music, literature, and other art forms embody the essence of human wisdom and induce esthetic experience, among which poetry is inherently creative because it contains a wealth of symbols, imageries, insights, and so forth. The appreciation and learning of Chinese poetry is an important part of the curriculum at the secondary level. However, studies have mainly focused on the textual characters of poetry, with little literature focusing on the esthetic appreciation and in-depth learning of poetry. In this vein, we ask whether emotional design will promote the appreciation of Chinese poetry. To answer this question, we explored the influence of the combination of external emotion induction (positive and neutral movie clips) and internal emotional design (chromatic and achromatic) on esthetic preference and learning of poetry. One hundred and sixty-six participants (14–15 years old) were randomly assigned to one of four conditions created by two factors (external emotion induction and internal emotional design). The results showed that the combination of external emotion induction and internal emotional design promoted learners’ positive emotions, retention, and transfer performances. Furthermore, learners’ perceived difficulty decreased significantly when external emotional induction and internal emotional design were both positive. Consequently, these findings indicated that emotional design in multimedia facilitated the learning performance of middle school students in Chinese poetry, and supported the Cognitive-Affective Theory of Learning with Media. This research was a preliminary exploration of emotional design in humanities.